2023
DOI: 10.1007/s10067-023-06576-x
|View full text |Cite
|
Sign up to set email alerts
|

Low estimated glomerular filtration rate is an independent risk factor for higher hydroxychloroquine concentration

Abstract: Background The aim of this study was to analyze the relationship of the estimated glomerular filtration rate (eGFR) to hydroxychloroquine (HCQ) blood concentrations in systemic lupus erythematosus (SLE) patients. Method Patients with SLE who had been taking HCQ for more than 12 months were recruited. All subjects gave written informed consent. Various clinical characteristics and laboratory values were examined. The blood concentration of HCQ was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…More studies are required to enable clinicians to individualise these therapies via TDM in SLE. -Age [25] -Gender [25] -CYP450 polymorphisms [26,27] -Renal function [23,30] -Ethnicity [52] -Renal function [53] -Liver function [51] -Serum albumin levels [51] -Concomitant drugs (e.g., proton pump inhibitors, iron oxide) [51] -CYP3A inhibitors or inducers including dietary polyphenols -CYP3A5 polymorphisms [70] -Xanthine oxidase inhibitor -TPMT/NUDT15 polymorphisms [84] Utility of monitoring -Identify non-adherence, which predicts damage [39] and mortality -Predicts lupus flares and treatment failure [34,35] -Predicts thrombotic events [40] -Predicts HCQ retinopathy [41] Determine…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies are required to enable clinicians to individualise these therapies via TDM in SLE. -Age [25] -Gender [25] -CYP450 polymorphisms [26,27] -Renal function [23,30] -Ethnicity [52] -Renal function [53] -Liver function [51] -Serum albumin levels [51] -Concomitant drugs (e.g., proton pump inhibitors, iron oxide) [51] -CYP3A inhibitors or inducers including dietary polyphenols -CYP3A5 polymorphisms [70] -Xanthine oxidase inhibitor -TPMT/NUDT15 polymorphisms [84] Utility of monitoring -Identify non-adherence, which predicts damage [39] and mortality -Predicts lupus flares and treatment failure [34,35] -Predicts thrombotic events [40] -Predicts HCQ retinopathy [41] Determine…”
Section: Discussionmentioning
confidence: 99%
“…Yet, blood HCQ concentrations are profoundly affected by renal function. Several studies including the PLUS study found an inverse correlation between the estimated glomerular filtration rate (eGFR) and blood HCQ concentrations [23,30]. The Joint European League Against Rheumatism and European Renal Association-European Dialysis and Transplant Association (EULAR/ERA-EDTA) guidelines recommend that the maximum dosing of HCQ is 5 mg/kg/day, and that the dose be reduced by 50% when eGFR < 30 mL/min [31].…”
Section: Hydroxychloroquine (Hcq)mentioning
confidence: 99%